#MeToo...or not? Do salient shocks affect gender social norms? - Manuel E. Lago (University College Dublin, UCD School of Economics, 2023)
Previous research has documented the importance and persistence of social norms, but there is limited understanding of whether they are capable of changing in the short run. Utilizing data from Sweden and Denmark, this article addresses this gap by testing whether significant local shocks may push societies toward deviating from their social norm. In Sweden, the country was particularly shocked by allegations of sexual harassment against Jean-Claude Arnault on November 24, 2017, which led to salient discussions about systematic gender-related violence and harassment. This paper estimates the impact of the Jean Arnault scandal on attitudes toward women's rights by exploiting survey data from the European Values Study. Using both a regression discontinuity and a difference-in-differences approach, I find a sharp improvement in Swedish attitudes toward women's rights after the scandal, while no significant change is identified in Denmark. These contrasting results demonstrate how the absence of a significant local shock may explain the stability of social norms in similar countries.
Keywords: J16; Z13; 330; Social norms; measuring norms; gender inequality; gender attitudes; #MeToo movement